DASAR PENGUATKUASAAN DAN PENDAKWAAN JENAYAH SYARIAH DI MALAYSIA: SATU ANALISIS - Ismail, Siti Zubaidah (Jurnal Syariah, 2008)
Enforcing the Shariah criminal offences enactment is the prime duty of the religious enforcement officers. In doing so, a standard operating procedure (SOP) is needed apart from the existing Shariah criminal procedure enactment. Without it, efforts of enjoining rights and forbidding wrong doings tend to be mistaken for moral policing and the enforcement of personal standards onto others. This article discusses the importance of SOP for religious enforcement officers and its relevance in handling Shariah criminal cases before investigation papers are handed over to Syarie prosecutors.